Interesting low temperature magneto-elastic behavior of a FINEMET metglass - Md. Sarowar Hossain; M. A. Hakim; P. K. Mukhopadhyay (AIP Advances, 2017)
We here report on studies of low temperature dynamic elastic properties of an amorphous ribbon of a FINEMET alloy, with and without magnetic field. Characterization with XRD and SEM showed that the sample was partially amorphous. Magnetization study showed the system as ferromagnetic and there was no transition in resistivity, anomalous peaks in sound velocity and internal friction measurements, with a small hysteresis and strong magnetic field dependence, were found in this temperature range. After analysing the data we concluded that it was magnetic in origin. This is reported for the first time in the FINEMET system.